Recent Advances in Pancreatic MR Imaging: A Guide on How, When, and Why to Perform - Sivasubramanian Srinivasan; Argha Chatterjee (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Imaging of the pancreas is often challenging because of its retroperitoneal location and unique set of pathologies. Conventional imaging modalities, such as transabdominal and endoscopic ultrasonography (EUS), computed tomography (CT), and magnetic resonance imaging (MRI), are well described in the literature. However, with modern demand for functional and molecular information from imaging studies, newer imaging modalities and modifications of existing modalities are developed. MRI is widely used as a problem-solving tool in pancreatic pathologies. Magnetic resonance cholangiopancreatography (MRCP) is an excellent technique for the depiction of the pancreatic ductal or biliary ductal pathologies. Newer modification of MRI including secretin MRCP, advanced diffusion-weighted imaging (DWI), perfusion imaging, and tissue composition analysis (fat and fibrosis quantification) add to the arsenal of MRI of the pancreas. In this review, we discuss the evolution of MRI of the pancreas and clinical application of advanced MR sequences.